2022
DOI: 10.1002/iju5.12494
|View full text |Cite
|
Sign up to set email alerts
|

Liesegang rings in the setting of end‐stage renal disease

Abstract: Introduction: Liesegang rings are acellular, lamellar, concentric rings of organic or inorganic material naturally formed in both biologic and environmental systems. Description in human tissue is scarce. Liesegang rings have exclusively been identified in association with pathologic disease processes and thus are not typically considered in differential diagnosis. They are usually described with cystic or inflammatory lesions. Histologically, Liesegang rings show features that are also seen in sections of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In vivo LRs are primarily formed in supersaturated colloidal systems, and cystic or inflammatory processes could potentially play a role in the formation of this environment. 7 Although the mechanism related to LR formation in this case could not be elucidated, it is possible that long-term retention of secretions and degenerated materials in the dilated bronchi may be related to their formation.…”
Section: Brief Reportmentioning
confidence: 89%
See 1 more Smart Citation
“…In vivo LRs are primarily formed in supersaturated colloidal systems, and cystic or inflammatory processes could potentially play a role in the formation of this environment. 7 Although the mechanism related to LR formation in this case could not be elucidated, it is possible that long-term retention of secretions and degenerated materials in the dilated bronchi may be related to their formation.…”
Section: Brief Reportmentioning
confidence: 89%
“…Fewer than 30 cases of LRs have been reported in the English literature. [2][3][4][5][6][7][8] Herein, we describe an exceptional case of LRs associated with allergic bronchopulmonary aspergillosis and review the reported literature for histopathological features of LRs.…”
mentioning
confidence: 99%